Species Composition and Visiting Frequencies of Flower Visitors of Chromolaena odorata in a Dry Zone Forest Patch of Sri Lanka - D. G. R. M. M. Kaushalya Rathnayake; W. M. G. Asanga S. T. B. Wijetunga (Psyche: A Journal of Entomology)
Plant-animal interaction has been a major theme in ecology as it has helped ecologists to rule out different patterns they observed in the surrounding environments. Chromolaena odorata is another plant species that is studied extensively as it has become a major troublesome weed in many parts of the tropics. But, handful of studies are available on pollination of this invasive plant species in dry forests and its function as a pollinator sink in these environments. The current study was carried out in a dry zone secondary forest patch in North-Central Sri Lanka to assess the diversity, abundance, and pollination strength of flower visitors associated with the C. odorata. The results suggest that the diversity of Hymenoptera and Lepidoptera is higher than the other insect orders that visited C. odorata, but all species exerted equal pollination strength on the plant. The attraction of large numbers of insects is concluded to as one of the factors that contribute to the reproductive success of C. odorata in dry zone forests.